2007
DOI: 10.1007/s00455-007-9079-2
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Evaluation Practices of Speech and Language Therapists in Ireland: Clinical Assessment and Instrumental Examination Decision-Making

Abstract: Abstract. The purpose of this study was to investigate clinical assessment practices and instrumental examination decision-making by speech and language therapists (SLTs) in Ireland. A 21-question survey (including patient scenarios) was sent to 480 SLTs in Ireland. A total of 261 completed surveys were returned (54%), providing demographic information on SLTs currently working in Ireland and their services. Of these 261 surveys, 70 provided the data for the study, focusing on SLTs currently working in dysphag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 22 publications
2
36
0
5
Order By: Relevance
“…The questionnaire used in the current study was developed through modifications and adaptations of available published surveys and guidelines in the area of speech-language pathology (Bateman, Leslie, & Drinnan, 2007;Martino, Pron, & Diamant, 2004;MathersSchmidt & Kurlinski, 2003;O'Donoghue & Dean-Claytor, 2008;Pettigrew & O'Toole, 2007;Speech Pathology Australia, 2004;Ward, Jones, Solley, & Cornwell, 2007). Prior to distribution, clarity and content of the questionnaire was validated by a group of Malaysian and Australian SLPs.…”
Section: Questionnairementioning
confidence: 99%
“…The questionnaire used in the current study was developed through modifications and adaptations of available published surveys and guidelines in the area of speech-language pathology (Bateman, Leslie, & Drinnan, 2007;Martino, Pron, & Diamant, 2004;MathersSchmidt & Kurlinski, 2003;O'Donoghue & Dean-Claytor, 2008;Pettigrew & O'Toole, 2007;Speech Pathology Australia, 2004;Ward, Jones, Solley, & Cornwell, 2007). Prior to distribution, clarity and content of the questionnaire was validated by a group of Malaysian and Australian SLPs.…”
Section: Questionnairementioning
confidence: 99%
“…Cervical auscultation is increasingly being used to supplement clinical swallowing assessment. The sounds associated with swallowing have been investigated using accelerometers and microphones for acoustic characteristics and possible prediction of aspiration (10,14,17,26,27) . The use of cervical auscultation varies in its reported reliability, and validity in terms of comparison to videofluoroscopic swallow study (VFSS) (17,25,27,28) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the suggestion that these patterns are non-random is supported by the considerable similarity across self-report studies regarding the components that 90% of SLPs across Ireland, the UK, the USA and Australia reported that they do 'usually/always' use (see Table 1) [7][8][9][10][11]. Across these studies, it has been speculated that components may have been less frequently used because the research evidence is not strong or has ruled them out as irrelevant (e.g., gag reflex, cervical auscultation), the survey components were ambiguous (e.g., whether speech and language screening was conducted meant informally or via a standardised assessment) or SLPs may not have had access to required training (e.g., indirect laryngoscopy).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is considerable variation with regard to the components SLPs self-report as routinely included in this assessment process [7][8][9][10][11]. The few standardised protocols available are either screening tools [12,13] or have been validated only on patients poststroke [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation